2013
DOI: 10.1186/1756-9966-32-83
|View full text |Cite
|
Sign up to set email alerts
|

Everolimus-induced human keratinocytes toxicity is mediated by STAT3 inhibition

Abstract: BackgroundMammalian target of rapamycin (mTOR) inhibitors are associated with dermatological adverse events. The chief aim of this study was to examine the relation between the signal transducer and activator of transcription 3 (STAT3) protein and the dermatological adverse events associated with the mTOR inhibitor everolimus.MethodsWe evaluated the effects of STAT3 activity and related signal transduction activities on everolimus-induced cell growth inhibition in the human keratinocyte HaCaT cell line via a W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…Inhibition of mTOR kinases affects signalling pathways regulating cell cycle and growth, angiogenesis and tissue repair . The skin is an unwanted target experiencing several side‐effects, and experimental data have postulated a direct mTOR activity on human keratinocytes altering the downstream signalling pathway . Influences on intracellular functions, such as motility and adhesion or desmosomal junctions assemblage might be relevant in the induction of the bullous autoimmune disease.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Inhibition of mTOR kinases affects signalling pathways regulating cell cycle and growth, angiogenesis and tissue repair . The skin is an unwanted target experiencing several side‐effects, and experimental data have postulated a direct mTOR activity on human keratinocytes altering the downstream signalling pathway . Influences on intracellular functions, such as motility and adhesion or desmosomal junctions assemblage might be relevant in the induction of the bullous autoimmune disease.…”
Section: Discussionmentioning
confidence: 80%
“…[1][2][3][4] The skin is an unwanted target experiencing several side-effects, and experimental data have postulated a direct mTOR activity on human keratinocytes altering the downstream signalling pathway. 13 Influences on intracellular functions, such as motility and adhesion or desmosomal junctions assemblage might be relevant in the induction of the bullous autoimmune disease. Another case of BP in a kidney-transplanted patient has been reported in Italy, in which everolimus was suspected and withdrawn, but at the moment of the publication the patient was still under corticosteroid therapy, and rechallenge was not performed.…”
Section: Discussionmentioning
confidence: 99%
“…The vascular endothelial cell-keratinocyte axis is a novel insight into the mechanism underlying drug-induced cutaneous diseases, given that a majority of previous studies have only identified the keratinocyte as the primary regulator of drug-specific dermatological toxicities. [20][21][22] In fact, due to the complex internal structures and functions of organisms, drugs may not always directly influence their effector cells and immediately give rise to pathological processes. Intricate cases of crosstalk were reported to occur among different types of cells at the onset of various drug toxicities, such as doxorubicin-induced cardiotoxicity and bleomycin-induced pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Hyper-keratosis, including hyper-proliferation and hyper-differentiation, arises from the epidermal dyshomeostasis in keratinocytes. [16][17][18][19] Given that most cutaneous toxicities induced by drugs (e.g., everolimus, adriamycin liposome, and capecitabine) are caused by cellular processes targeting keratinocytes, [20][21][22] we initially sought to test the direct effect of sorafenib on keratinocytes by employing human primary keratinocytes and HaCaT cells, the immortalized human keratinocytes which largely retained the differentiation capacity of normal epidermal cells. 24 We examined the states of proliferation and differentiation in keratinocytes, with keratin 5 (KRT5) and keratin 14 (KRT14) applied as proliferation markers, and keratin 1 (KRT1), keratin 10 (KRT10), loricrin (LORICRIN) and involucrin (IVL) characterizing differentiation.…”
Section: Vascular Endothelial Cells Contribute To Sorafenib-induced Hmentioning
confidence: 99%
See 1 more Smart Citation